Artificial Intelligence and the Formation of Islamic Character: A Spiritual Ethics Perspective in Madrasah Ibtidaiya - Ahmad Fauzi; Rahmat Saputra; Rahmah Diani; Uswatun Hasanah (Institut Attanwir Bojonegoro, 2026)
The rapid development of Artificial Intelligence (AI) has significantly influenced contemporary educational practices, including at the level of primary education. This technological transformation presents both opportunities and challenges for Islamic educational institutions, particularly Madrasah Ibtidaiyah, in maintaining the balance between technological innovation and the cultivation of Islamic character grounded in spiritual ethics. The increasing integration of digital technologies into learning environments raises concerns regarding the preservation of moral and spiritual values that constitute the core objectives of Islamic education. Therefore, this study aims to analyze the role and potential of Artificial Intelligence in supporting the formation of Islamic character in Madrasah Ibtidaiyah, to formulate a framework of spiritual ethics as a normative foundation for the use of AI in Islamic education, and to provide practical recommendations for educators and educational institutions in utilizing AI in ways that remain aligned with Islamic values. This research employs a Systematic Literature Review (SLR) approach, which systematically examines relevant academic literature related to Artificial Intelligence in education, Islamic character education, and spiritual ethics within Islamic educational contexts. The research data were obtained from scholarly sources such as peer-reviewed journal articles, academic books, and previous scientific studies, which were analyzed through content analysis to identify patterns, conceptual relationships, and key insights relevant to the research objectives. The findings reveal that Artificial Intelligence has considerable potential to enhance instructional innovation and learning effectiveness in Madrasah Ibtidaiyah; however, its implementation must be guided by a framework of spiritual ethics to ensure that technological utilization remains consistent with the fundamental mission of Islamic education in cultivating morally responsible and spiritually aware students